Using Joint Interviews With Family Members as Key Informants on Shared Social Identities: A Case of Coloured Identities - Errolyn L. Gordon (International Journal of Qualitative Methods)
Joint interviews are a qualitative data collection method conducted by one researcher with two or more participants who share a pre-existing relationship and a common experience. This paper examines critically the application of joint interviews with families, using, as example, my doctoral study, which explored the construction of coloured women’s identities in Cape Town, South Africa. While the research explored coloured identities, the primary focus in this paper is on the methodological insights gained through joint interviews with family members. Positioning the study in the existing academic discourse on joint interviews, this paper highlights their potential to uncover relational dynamics, co-constructed meanings, and collective storytelling in family units. In this paper, I provide a sense of how a researcher might experience and engage with the process subjectively. I argue that joint interviews can offer valuable information about how families co-construct meaning and share experiences. Key methodological findings demonstrate that joint interviews can elicit rich, multi-voiced stories that reveal practices and processes through which histories, generations, and identities are shared (or not) jointly. Challenges are addressed in managing dominant voices, group dynamics, and ethical issues. This paper contributes to qualitative research by expanding the scope of joint interviews beyond couples to family members, providing insight into their strengths and limitations, and practical tips for their use. These practical tips are especially beneficial in studies with marginalised communities and complex social identities, equipping researchers with the necessary tools to navigate the challenges and complexities of joint interviews.